Contributions of District Health Information Software 2 (DHIS2) to maternal and child health service performance in Ethiopia: An interrupted time series mixed-methods study - Zerfu, Taddese Alemu; Asressie, Moges; Tareke, Amare Abera; Begna, Zenebu; Habtamu, Tigist; Werkneh, Netsanet; Nigatu, Tariku; Jisso, Meskerem; Genta, Addisalem (BioMed Central, 2025)
Background The District Health Information Software 2 (DHIS2) is the primary digital platform for health management information systems (HMIS) in Ethiopia, aligning with the nation’s digitization strategy. Despite widespread implementation, its effectiveness on key health service indicators, particularly maternal and child health (MCH) services, remain unclear.